Assessment of Replacing Gas Boilers with Heat Pumps for Hot Water Preparation in Car Washes - Talaba Ovidiu; Serban Alexandru; Hiris Paul Daniel; Balan Mugur Ciprian (E3S Web of Conferences)
The study provides a complex analysis for replacement of the natural gas boilers with air to water heat pumps, as the heat source for the hot water to be used in the car washing machines. It was considered heat pumps with R744 and with R290 as refrigerant, and it was proved that even heat pumps that seem to be undersized at negative temperatures, can still provide the required heat for 70 % of the full operating time. The feasibility was determined to be higher for the heat pumps with R290 and the payback period is lower than 2 years for the average car washing frequency of less than 5 cars washed / hour. The hot water storage tank can increase the period of continuous operation even at negative ambient temperature when the heat pump seems to be undersized.